Coverage dependent disorder-order transition of 2H-tetraphenylporphyrin on Cu(111) - Stark, Michael Werner; Ditze, Stefanie; Drost, Martin; Buchner, Florian; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2013)
In this study, we investigate the peculiar coverage dependent supramolecular arrangement of 2H-tetraphenylporhpyrin (2HTPP) on Cu(111) with scanning tunneling microscopy at room-temperature. At low coverage, "slow" diffusion of individual 2HTPP molecules along the close-packed atomic rows of the substrate is observed, and no supramolecular ordering occurs. However, at higher coverage, the formation of ordered, checkerboard-like domains is found, with two molecules per unit cell at different distances from the surface. This behavior is attributed to a complex interplay of site specific molecule-substrate interaction, mainly the strong interaction between the iminic N atoms and Cu substrate atoms, with intermolecular T-type and π-π interactions. © 2013 American Chemical Society.